2005
DOI: 10.1016/s1472-6483(10)61143-1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and obstetric outcome of pregnancies conceived by ICSI or IVF

Abstract: Intracytoplasmic sperm injection (ICSI) is currently widely used despite concern regarding pregnancy complications and outcome, specifically congenital malformations. The aim of this study was to compare the obstetric and neonatal outcome of pregnancies conceived by IVF and ICSI. Long-term follow-up was achieved through questionnaires sent to women who conceived after IVF/ICSI treatment. Information was obtained regarding 219 pregnancies (322 children) conceived after ICSI and 145 pregnancies (201 children) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
3
5
0
2
Order By: Relevance
“…The results demonstrated that birth weight was significantly lower in the ART group than in the SC group, which is in agreement with the results of other studies [2123]. Some followup studies of ART-conceived children suggest that low birth weight is due to multiple pregnancies.…”
Section: Resultssupporting
confidence: 91%
“…The results demonstrated that birth weight was significantly lower in the ART group than in the SC group, which is in agreement with the results of other studies [2123]. Some followup studies of ART-conceived children suggest that low birth weight is due to multiple pregnancies.…”
Section: Resultssupporting
confidence: 91%
“…Whether the genes identified here can be powerful predictors of birth weight requires a larger study, which is currently underway. Lower average birth weight has been repeatedly reported from ART compared with natural conception (30)(31)(32), and our results may indicate that cumulus biomarkers can identify gametes more likely to result in live birth with improved developmental potential.…”
Section: Discussionsupporting
confidence: 68%
“…Two of the children were born prematurely and with low birth weight, and the health of one pair of twins was rated as 5 (out of 1-10). The latter results recall similar findings on neonatal outcomes of pregnancies conceived by IVF (34).…”
Section: Discussionsupporting
confidence: 88%